Biofilm producing plant growth promoting bacteria in combination with glycine betaine uplift drought stress tolerance of maize plant - Yasmeen, Tahira; Arif, Muhammad Saleem; Tariq, Mohsin; Akhtar, Sadia; Syrish, Afira; Haidar, Waqas; Rizwan, Muhammad; Hussain, Muhammad Iftikhar; Ahmad, Ajaz; Ali, Shafaqat (Frontiers in Plant Science, 2024)
The escalating threat of drought poses a significant challenge to sustainable food production and human health, as water scarcity adversely impacts various aspects of plant physiology. Maize, a cornerstone in staple cereal crops, faces the formidable challenge of drought stress that triggers a series of transformative responses in the plant. The present study was carried out in two sets of experiments. In first experiment, drought stress was applied after maintaining growth for 45 days and then irrigation was skipped, and plant samples were collected at 1 st , 3 rd and 6 th day of drought interval for evaluation of changes in plant growth, water relation (relative water content) and antioxidants activity by inoculating indigenously isolated drought tolerant biofilm producing rhizobacterial isolates (Bacillus subtilis SRJ4, Curtobacterium citreum MJ1). In the second experiment, glycine betaine was applied as osmoregulator in addition to drought tolerant PGPR to perceive modulation in photosynthetic pigments (Chlorophyll a and b) and plant growth under varying moisture stress levels (100, 75 and 50% FC). Results of the study revealed upsurge in root and shoot length, fresh and dry biomass of root and shoot besides increasing chlorophyll contents in water stressed inoculated plants compared to uninoculated plants. Glycine betaine application resulted in an additional boost to plant growth and photosynthetic pigments, when applied in combination with bacterial inoculants. However, both bacterial inoculants behaved differently under drought stress as evident from their biochemical and physiological attributes. Isolate SRJ4 proved to be superior for its potential to express antioxidant activity, leaf water potential and relative water contents and drought responsive gene expression while isolate MJ1 showed exclusive increase in root dry biomass and plant P contents. Though it is quite difficult to isolate the bacterial isolates having both plant growth promoting traits and drought tolerance together yet, such biological resources could be an exceptional option to be applied for improving crop productivity and sustainable agriculture under abiotic stresses. By exploring the combined application PGPR and glycine betaine, the study seeks to provide insights into potential strategies for developing sustainable agricultural practices aimed at improving crop resilience under challenging environmental conditions.